LA EDUCACIÓN DE EL DE ERUDITIONE FILIORUM NOBILIUM DE VICENTE DE BEAUVAIS (1190-1264) - Vergara Ciordia, Javier (Educación XX1, 2012)
El presente artículo analiza la educación de la mujer en el De eruditione filiorum nobilium de Vicente de Beauvais (1246). Una obra latina, prácticamente inédita, que puede considerarse el primer tratado de pedagogía sis- temática escrito en el mundo medieval. Su cuarta parte, dedicada al estudio de la educación de la mujer como doncella, esposa, viuda y virgen consagrada, re- presenta, quizás, la expresión más acabada y sistemática sobre educación fe- menina escrita hasta entonces por un hombre de Iglesia. Para su elaboración se han tenido presentes el manuscrito latino Md, de de España (B. N. 10254 (Ii 2) (XIV), f. 65-118v.).), y el manuscrito latino P, de de Francia (Biblioteca Nacional de París, B. N. Lat. 16390). Su estudio, traducción y cotejo nos ha permitido ofrecer una de las síntesis más representativas y tempranas de la cultura escolástica sobre educación de la mujer.ABSTRACT The present article analyzes the education of woman in the De Eruditione Filiorum Nobilium of Vicente de Beauvais (1246). This academic work is a Latin literary piece, virtually unprecedented, that can be considered the first treatise of systematic pedagogy conceived in the Medieval times. The fourth chapter of this treatise, devoted to the analysis of the education of woman as maiden, wife, widow and virgin represents, most probably, the most well finished and systematic academic writting concerning feminine education up to this historical moment conceived and expressed by a clergy-man. In the elaboration of this academic work the author has considered key and most relevant documents such as the Md. Latin manuscript of the Biblioteca Nacional de Madrid, and the P. Latin manuscript of the Biblioteque Nationale de France. The study, analysis, translation and comparition of these literary works has enabled the author to form one of the most early versions and most representative synthesis of the scholastic culture on the subject of the education of women.